Pb(NO3)2 induces cell apoptosis through triggering of reactive oxygen species accumulation and disruption of mitochondrial function via SIRT3/SOD2 pathways - Lin, Hui‐Wen; Lee, Hsiang‐Lin; Shen, Ting‐Jing; Ho, Meng‐Ting; Lee, Yi‐Ju; Wang, Inga; Lin, Ching‐Pin; Chang, Yuan‐Yen (Environmental toxicology, 2024)
Lead (Pb) is nonbiodegradable and toxic to the lungs. To investigate the potential mechanisms of Pb‐induced reactive oxygen species (ROS) accumulation and cell death in the lungs, human non‐small lung carcinoma H460 cells were stimulated with Pb(NO3)2 in this study. The results showed that Pb(NO3)2 stimulation increased cell death by inducing cell apoptosis which showed a reduced Bcl‐2 expression and an enhanced caspase 3 activation. Pb(NO3)2 also caused the production of H2O2 in H460 cells that triggering the buildup of ROS and mitochondrial membrane potential loss. We found that Pb(NO3)2 modulates oxidoreductive activity through reduced the glutathione‐disulfide reductase and glutathione levels in Pb(NO3)2‐exposed H460 cells. Furthermore, the superoxide dismutase (SOD) upstream molecule sirtuin 3 (SIRT3) was increased with Pb(NO3)2 dose. Collectively, these results demonstrate that Pb(NO3)2 promotes lung cell death through SIRT3/SOD‐mediated ROS accumulation and mitochondrial dysfunction.